Exercise pressor reflex function following acute hemi-section of the spinal cord in cats - Murphy, Megan N.; Ichiyama, Ronaldo M.; Iwamoto, Gary A.; Mitchell, Jere H.; Smith, Scott A. (Frontiers in Physiology, 2013)
Cardiovascular disease is a leading cause of morbidity and mortality in patients post spinal cord injury (SCI). The prescription of exercise as a therapeutic modality for disease prevention in this population is promising. It is logical to suggest that the sooner an exercise program can begin the more benefit the patient will receive from the therapy. However, the time point after injury at which the requisite circulatory responses needed to support exercise are viable remains largely unknown. The skeletal muscle exercise pressor reflex (EPR) significantly contributes to cardiovascular control during exercise in healthy individuals. Experiments in patients with a chronic lateral hemi-section of the spinal cord (Brown-Séquard syndrome) suggest that the EPR, although blunted, is operational when examined months to years post injury. However, whether this critically important reflex remains functional immediately after lateral SCI or, in contrast, experiences a period of reduced capacity due to spinal shock has not been established. This study was designed to assess EPR function after acute lateral transection of the spinal cord. The EPR was selectively activated in seven decerebrate cats via electrically stimulated static contraction of the triceps surae muscles of each hindlimb before and after lateral hemi-section of the T13-L2 region of the spinal cord. Compared to responses prior to injury, increases in mean arterial pressure (MAP) were significantly decreased when contracting the hindlimb either ipsilateral to the lesion (MAP = 17±3 mmHg before and 9±2 mmHg after) or contralateral to the lesion (MAP = 22±5 mmHg before and 12±4 mmHg after). The HR response to stimulation of the EPR was largely unaffected by induction of acute SCI. The findings suggest that the EPR maintains the ability to importantly contribute to cardiovascular regulation during exercise immediately following a Brown-Séquard-like injury.